Image Perception of Female Breast Beauty and Its Relation to 3D Anthropometric Measurements (Journal of Fiber Bioengineering and Informatics, 2018)
This study aimed to explore the relationship between breast shape measurements and breast beautyassessment. Breast Beauty Subjective Assessment System (BBSAS) was developed to evaluate the beautyof breasts. 75 female subjects aged 20-39 years were selected for assessment from the anthropometricdatabase of BIFT-Aimer Human Engineering Research Centre. 43 females working in intimate appareldesign were chosen as judges to answer a five-scale questionnaire using the BBSAS. 66 detailedmeasurements especially related to the breast region were also taken for investigation. Data analysisresults indicated that the breast beauty score was highly correlated with breast side view profile andbreast erectness. Beautiful breasts selected by judges had the following common characteristics: theratio of bust height to whole body height was 0.71; a triangle was constructed by front neck point, rightbust point and left bust point was an isosceles triangle with the top angle less than 60°. The regressionequation to predict the breast beauty scale was obtained based on key breast measurements. This studyprovides a new knowledge on relationship between the breast shape and breast beauty, as well as someuseful guidelines for bra design.